Humanism - Tony Davies (Routledge, 1997)
Humanism offers students a clear and lucid introductory guide to the complexities of Humanism, one of the most contentious and divisive of artistic or literary concepts. Showing how the concept has evolved since the Renaissance period, Davies discusses humanism in the context of the rise of Fascism, the onset of World War II, the Holocaust, and their aftermath. Humanism provides basic definitions and concepts, a critique of the religion of humanity, and necessary background on religious, sexual and political themes of modern life and thought, while enlightening the debate between humanism, modernism and antihumanism through the writings and works of such key figures as Pico Erasmus, Milton, Nietzsche, and Foucault.